Use of GIS and Remote Sensing to detect change along the coastline segment between Shkumbini and Semani rivers, central Albania - Bedini, E. (Bulletin of the Geological Society of Greece, 2007)
The coastline segment between Shkumbini and Semani rivers, in central Albania, is a very dynamic accumulative coastal environment. The position of the coastline in this segment is investigated with multi-temporal Landsat data of the years 1978-2001 integrated in a geographic information system. The analysis of the multitemporal remote sensing data shows that the coastline of this segment is subject to important changes during this short time interval. The study demonstrates the applicability and usefulness of historical Landsat data for change detection studies of the coastal environment.